2007
DOI: 10.2196/jmir.9.2.e10
|View full text |Cite
|
Sign up to set email alerts
|

Internet-Based Interactive Health Intervention for the Promotion of Sensible Drinking: Patterns of Use and Potential Impact on Members of the General Public

Abstract: Background Heavy drinking is responsible for major health and social problems. Brief interventions have been shown to be effective, but there have been difficulties in reaching those who might benefit from them. Pilot studies have indicated that a Web-based intervention is likely to be acceptable to heavy drinkers and may produce some health benefits. However, there are few data on how many people might use such a program, the patterns of use, and potential benefits.Objectives The aim was to examine the demogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
121
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(130 citation statements)
references
References 36 publications
6
121
1
Order By: Relevance
“…The low barriers to entering an online intervention (simple registration and completing of initial assessment) inflate attrition rates by including individuals exploring options but not ready to enter programs, or deciding programs are not suitable at time of registration. An evaluation of an online program for problem drinking found that of 10,000 users over a 27-month period, approximately one-third of users dropped out after the first week and usage declined each week with only 17% of users completing the six-week program (Linke, Murray, Butler, & Wallace, 2007). Reasons for dropping out appeared to vary, with some participants finding programs too timeconsuming or too challenging, or disengaging after early successful behavioural change (Linke et al, 2007;Strecher, Shiffman, & West, 2005).…”
Section: Implementation Issues For Online Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The low barriers to entering an online intervention (simple registration and completing of initial assessment) inflate attrition rates by including individuals exploring options but not ready to enter programs, or deciding programs are not suitable at time of registration. An evaluation of an online program for problem drinking found that of 10,000 users over a 27-month period, approximately one-third of users dropped out after the first week and usage declined each week with only 17% of users completing the six-week program (Linke, Murray, Butler, & Wallace, 2007). Reasons for dropping out appeared to vary, with some participants finding programs too timeconsuming or too challenging, or disengaging after early successful behavioural change (Linke et al, 2007;Strecher, Shiffman, & West, 2005).…”
Section: Implementation Issues For Online Interventionsmentioning
confidence: 99%
“…An evaluation of an online program for problem drinking found that of 10,000 users over a 27-month period, approximately one-third of users dropped out after the first week and usage declined each week with only 17% of users completing the six-week program (Linke, Murray, Butler, & Wallace, 2007). Reasons for dropping out appeared to vary, with some participants finding programs too timeconsuming or too challenging, or disengaging after early successful behavioural change (Linke et al, 2007;Strecher, Shiffman, & West, 2005). Client feedback from a Norwegian online therapy program for problem gambling found that a proportion had reached goals and reported diminished urges despite early attrition (Eidem, 2010).…”
Section: Implementation Issues For Online Interventionsmentioning
confidence: 99%
“…[2][3][4][5][6] While this strategy has the potential for low-cost widespread dissemination, access to ICT among certain groups such as urban women at high risk for HIV infection is variable. Characterizing ICT use is the first step in determining whether delivering interventions via these modalities is feasible.…”
Section: Introductionmentioning
confidence: 99%
“…Internetbased health interventions have been proven to be successful in conditions such as diabetes, heart failure, obesity, and substance abuse, among others. [1][2][3][4][5][6][7] In addition to medical applications delivered via the Internet, the Internet is becoming a major source of consumer health information. Surveys indicate that 64% of all Internet users in the United States engage in Internet health information seeking behavior (IHISB) and that 4% of all Internet searches are health related.…”
mentioning
confidence: 99%
“…2 Section of General Internal Medicine, Portland VA Medical Center, Portland, Oregon. 3 Division of General Internal Medicine & Geriatrics, 5 Departments of Medicine and Public Health & Preventive Medicine, Oregon Health Science University, Portland, Oregon.…”
mentioning
confidence: 99%